Gender and Right-Wing Populism: Analysing the Role of Women at the ministerial level - Lea Radke; Gila Rolofs (Acta Politologica, 2023)
The aim of this paper is to examine the role of women at the ministerial level in right-wing populist parties. To do so, we analyse the descriptive and substantive representation of women within the Hungarian and Polish right-wing populist cabinets. Using descriptive statistics, we examine the policy areas and relative prestige of their ministerial portfolios. To gain a deeper understanding of the role of women, we further provide an analysis of the roles of Beata Szydło as Polish prime minister and Katalin Novák as Minister without Portfolio for Families, Youth and the Elderly in Hungary. Within this analysis, we investigate their educational and political backgrounds and particularly focus on the gender aspects of their initiated family policies. Our results show that women within right-wing populist cabinets tend to govern traditionally ‘male’ and neutral policy areas; furthermore, they hold portfolios with similar prestige as do the men. The analysis of Beata Szydło and Katalin Novák indicates that women in executive offices are well educated and are more likely to become chief executives when their power is limited. Moreover, the investigation of the family policies demonstrates that they predominantly support the preservation of traditional family roles and strengthen them implicitly.